IDENTIFIKASI FAKTOR LINGKUNGAN PENYEBAB BANJIR BANDANG DI KABUPATEN ACEH TAMIANG - Siregar, Putri Fikadilah; Aswatul Sinurat, Dian; Ferah Yosantia, Muhammad; Rikza (Jurnal Media Teknik Sipil Samudra, 2025)
Flash floods are one of the hydrometeorological disasters that frequently occur in Aceh Tamiang Regency and cause significant impacts on the environment and civil infrastructure. Flash flood events are influenced by various interrelated environmental factors, both natural and anthropogenic. This study aims to identify the environmental factors contributing to flash floods in Aceh Tamiang Regency. The research employs a descriptive qualitative approach using secondary data obtained from relevant institutions and a comprehensive literature review. The results indicate that the main environmental factors triggering flash floods include high-intensity rainfall, changes in land cover in the upper watershed area, topographic conditions dominated by steep slopes, and limited river capacity due to sedimentation and inappropriate use of river buffer zones. These factors interact with one another and significantly increase the risk of flash flood occurrences. The identification of these environmental factors is expected to provide a scientific basis for flash flood mitigation planning through environmentally sound watershed management and sustainable civil engineering planning in Aceh Tamiang Regency.